Quantitative FRET measurement based on spectral unmixing of donor, acceptor and spontaneous excitation‐emission spectra. Issue 4 (26th December 2018) - Su, Wenhua; Du, Mengyan; Lin, Fangrui; Zhang, Chenshuang; Chen, Tongsheng
Abstract : The spontaneous excitation‐emission (ExEm) spectrum is introduced to the quantitative m ExEm‐spFRET methodology we recently developed as a spectral unmixing component for quantitative fluorescence resonance energy transfer measurement, named as SPEES‐FRET method. The spectral fingerprints of both donor and acceptor were measured in HepG2 cells with low autofluorescence separately expressing donor and acceptor, and the spontaneous spectral fingerprint of HEK293 cells with strong autofluoresence was measured from blank cells. SPEES‐FRET was performed on improved spectrometer‐microscope system to measure the FRET efficiency ( E ) and concentration ratio ( R C ) of acceptor to donor vales of FRET tandem plasmids in HEK293 cells, and obtained stable and consistent results with the expected values. Moreover, SPEES‐FRET always obtained stable results for the bright and dim cells coexpressing Cerulean and Venus or Cyan Fluorescent Protein (CFP)‐Bax and Yellow fluorescent protein (YFP)‐Bax, and the E values between CFP‐Bax and YFP‐Bax were 0.02 for healthy cells and 0.14 for the staurosporine (STS)‐treated apoptotic cells. Collectively, SPEES‐FRET has very strong robustness against cellular autofluorescence, and thus is applicable to quantitative evaluation on the protein‐protein interaction in living cells with strong autofluoresence. Abstract : The excitation‐emission spectrum ( S DA ) of a fluorescence resonance energy transfer sample is linearly unmixed into the four excitation‐emission spectral components of donor ( S D ), acceptor ( S A ), donor‐acceptor sensitization ( S S ) and autofluoresence ( S AU ).